Pola Resistensi Salmonella typhi yang Diisolasi dari Ikan Serigala (Hoplias malabaricus) terhadap Antibiotik - Waode Santa Monica; Hapsari Mahatmi; Kerta Besung (Veterinary Science and Medicine Journal, 2013)
The purpose of this study was to know the resistant pattern of Salmonella typhi (S. typhi) isolated from wolf fish (Hoplias malabaricus) to antibiotics in Bali Safari and Marine Park. S. typhi was isolated from fecal swab collected from the illness fish. The S. typhi was confirmed with MicrogenTM GN A ID test’s method. The antibiotic sensitivity of the S. typhi was tested using streptomycin, gentamicin, penicillin, vancomycin, and chloramphenicol according to the Kirby bouer method. The results showed that the isolate of S. typhi was resistant to penicillin and vancomycin, but sensitive to streptomycin, gentamicin, and chloramphenicol.